Pengaruh Kepatuhan Wajib Pajak UMKM Berdasarkan PP Nomor 23 Tahun 2018 Terhadap Penerimaan Pajak Di KPP Pratama Bojonagara - Cindy Amanda; Yeti Apriliawati (Indonesian Accounting Research Journal, 2020)
Type of research is quantitative. The population in this research are MSME taxpayer at KPP Pratama Bojonagara. The sample is set by incidental technique with as 100 MSME taxpayer respondents. The source of the data used in this research are primary data and secondary data. Data collection techniques in this research using questionnaires. This research uses statistical tools to process data, namely SPSS version 25. The results of this research prove that there is an effect of MSME taxpayer compliance based on PP No. 23 of 2018 on tax revenue at KPP Pratama Bojonagara. The results of the determination coefficient prove that the compliance of MSME taxpayers based on Government Regulation Number 23 of 2018 on tax revenue at KPP Pratama Bojonagara has an effect of 21.3% while the rest 78.7% is influenced by other variables.